Stackelberg and Marshall - Robson, Arthur J. (American Economic Review, 1990)
This paper advocates a generalized N-firm Stackelberg model as a plausible testable alternative description of oligopoly. A pure-strategy equilibrium must exist for this model. The main result is that efficiency obtains in the limit as the scale of each firm is shrunk relative to demand. This is demonstrated for the case of U-shaped average cost and also for that of natural monopoly.